Solid waste management and environmental awareness in a university com-munity, Trujillo-La Libertad: 2020 (SCIÉNDO INGENIUM, 2021)
The purpose of the research was to determine the relationship between solid waste management and environmental awareness in a university community, Trujillo-La Libertad: 2020. The population and sample consisted of 50 students belonging to a university community in Trujillo, two were employed Data collection instruments, being questionnaires on solid waste management and environmental awareness, the data were processed through graphs, to later describe their behaviors, also the relationship of variables was determined through the Spearman coefficient. A null correlation was obtained (0.169 –p: 0.05). The solid waste management according to dimensions were: knowledge about solid waste management, the value of 40 prevailed in "good", for practices on inert solid waste management the value of 42 prevailed in "good", and in attitude about Inert solid waste management the value of 49 predominated in "good". Environmental awareness according to the dimensions were: cognitive, had the pre-dominant value of 30 in "high", for affective the value of 39 predominated in "high", in The conative value of 42 predominated in "high" and finally, in the active dimension, there was a predominance of 41 "high".
Keywords: Management; solid waste; environmental awareness; university community